SELECTION PROCESS FOR AN AUTOMATED STORAGE SYSTEM: A UNISON FRAMEWORK APPROACH - Darmawan, Armin; Son, Nguyen Huu; Santoso, Halim Budi; Ping, Huang Yi (The South African Journal of Industrial Engineering, 2022)
An automated storage system (ASS) is a computer-controlled warehousing system that is used to manage and automatically pick and place parts/goods. A good automated storage system can maximise space and shorten shipments’ response time, thereby helping the company to adapt quickly to an ever-changing market. For many enterprises there is also an urgent need to establish and install ASS. However, many companies find it difficult to design and install the right ASS. Many considerations need to be examined in choosing a suitable ASS, given their various capacities and capabilities. This study aimed to employ the UNISON framework to present a comprehensive model for selecting the most suitable ASS. It identified two fundamental objectives in the ASS selection process: (1) choosing the most suitable design for ASS; (2) choosing the most competent vendor to build and implement the ASS. This study then broke the fundamental objectives down into more detailed mean objectives and attributes. After defining the mean objectives and attributes, the study created a key performance indicator to assess the selection process. An empirical study was conducted among small and medium-sized enterprises (SME) in Taiwan to validate the proposed framework. A qualitative study was then developed by interviewing three related stakeholders — the vice president, the head of the production department, and the senior engineer — to support the identification process in selecting and implementing the ASS. From this case study, we found that our ASS selection model showed good practical viability.